Mengungkap Kekuatan Perceived Organizational Support dan Servant Leadership terhadap Employee Performance: Eksplorasi Work Engagement sebagai Mediator Kunci di Sektor Publik - Aditya Pradipta, Daniel; Savitri Pusparini, Elok (IPB University, 2023)
The evolving dynamics of work influenced by the Fourth Industrial Revolution and the aftermath of the COVID-19 pandemic have compelled management to formulate precise strategies for the proficient management of human resources (HRM) to ensure the continued optimal performance of organizations. This paradigm extends its applicability to the public sector, where the position and functions of Civil Servants (ASN) within governmental bodies are of paramount importance in the execution of national development initiatives. Thus, this research endeavor seeks to investigate the relationship between perceived organizational support (POS) and servant leadership concerning employee performance, with work engagement serving as a mediating factor within the context of ASN employed by Financial Management Institutions within the public sector. The study was conducted through the administration of a questionnaire survey to 305 ASN respondents situated at the Central Office of the Financial Management Institution, employing the Covariance Based – Structural Equation Modeling (CB-SEM) technique for data analysis. The research findings manifest that both POS and servant leadership exhibit a significantly positive influence on work engagement. Moreover, work engagement serves as a complete and significant mediator in the relationship between POS and servant leadership, affecting employee performance in a significantly positive manner. This research contributes to managerial implications that can be applied within organizations, leadership circles, and among individuals within the public sector, concerning the interrelated concepts of POS, servant leadership, work engagement, and employee performance.